Voices from the Archipelago: Empowering Cultural Identity and Engagement through Responsive Bilingual Narratives in EFL Classrooms - Alprin Matitaputty; Hendrik J. Maruanaya; Wenda M. Kakerissa (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study explores how culturally responsive bilingual narratives support students’ cultural identity and engagement in English as a Foreign Language (EFL) classrooms. Using a qualitative exploratory design supported by complementary quantitative data, the research involved 17 eighth-grade students from a public junior high school in Ambon, Maluku. Data were collected through classroom observation, semi-structured interviews, reflective journals, artifact analysis, and a post-instruction feedback questionnaire. Qualitative data were analyzed thematically, while quantitative data were examined using descriptive statistics and reliability testing. The findings show that culturally responsive pedagogy-based bilingual narratives increased student engagement, reduced language anxiety, and strengthened cultural pride. Students also found the learning materials meaningful, relevant, and easier to understand because they connected English learning to local cultural experiences. The questionnaire demonstrated high internal consistency (Cronbach’s Alpha = 0.87), indicating reliable support for students’ perceptions of the instructional materials. Rather than assessing language proficiency, the questionnaire was intended to capture students’ responses to the learning experience and the cultural relevance of the materials used in class. The study further highlights that integrating local cultural narratives into bilingual learning materials can create a more inclusive and emotionally supportive classroom environment, particularly in archipelagic and multilingual educational settings. These findings contribute to the limited body of research on culturally responsive bilingual instruction in Indonesian EFL contexts and emphasize the pedagogical importance of integrating local identity, language, and culture into English language teaching practices.